Photophysical properties of electroluminescent molecules based on thiophene and oxadiazole. Computational investigations - Fatima Agda; Diae Nebbach; Tayeb Abram; Mohammed Bouachrine; Mustapha Taleb (Results in Chemistry, 2020)
In this work, we use the DFT calculation to investigate the photophysical properties of three compound organic light-emitting diodes. These new compounds based on thiophene, oxadiazole, and TPA, whose structure is donor-π-acceptor (D-π-A). To investigate the relationship between the structures and properties optic of these electroluminescent materials we optimize the ground state and the excited state to determine the relationship between the geometrical and optical properties. The calculation of ionization potential and electronic affinity shows that the D2 molecule has the lowest value of IP. The molecule D2 has the highest value for λtotal. These results show that the electron transport capacity is less than the hole transport capacity. This calculation shows that the compounds with PA structure own interesting characteristics in terms of IP, AE and reorganization energy. Thus, that these compounds present the best performance for electroluminescence devices. The emission properties show that the compounds can be used as blue and yellow emitters electroluminescent.